ULTRASONIC TOMOGRAPHY MODELING IN ISOTROPIC AND ANISOTROPIC CRYSTALS MEDIA - MUTIA SARI (NIM : 22310304); Pembimbing : Dr. Eng. T. A. Sanny, VANI
This study discusses about ultrasonic tomography method in isotropic and anisotropic crystals media. Media in the form of rock slice (synthetics case). The rock has a base mass is clay, in which minerals are plagioclase, orthoclase, and olivine, and the presence of voids. Anisotropy represented by maximum velocity, minimum velocity, and minerals orientation. Rocks with different mineral reconstructed using tomography reconstruction algorithms, Back Projection Technique (BPT), Simultaneous Iterative Reconstruction Technique (SIRT), and Modified Iterative Reconstruction Technique Simultaneous (MSIRT) to obtain images of internal velocity distribution (tomogram). The research was done to accelerate the determination of the composition of rocks, without damaging the rock. Initially, software calibration performed using the directly initial slowness from the velocity model to SIRT and MSIRT algorithm. Then, the initial slowness varied using the average velocity, BPT velocity, and seismic velocity anisotropy. As for the BPT algorithm, slowness variation is not done earlier because the algorithm uses the average slowness of each raypath. Reconstruction results of this study provide information that tomography reconstruction algorithm able to detect the presence of other minerals in the rock. The best result was shown by MSIRT algorithm with the initial slowness from seismic velocity anisotropy, which can reconstruct the position and shape of the mineral right. It can be seen visually and from the resulting reconstruction error.